(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The Guisando Bulls Agreement, in which Elisabeth the Catholic was reecognized and proclaimed Princess Heiress of the Kingdoms of Leon and Castilla on September 19th, 1468, is the origin and star point of her Reign (1474-1504). The document that contains the stated Pact is analyzed in this article. The original text hasn´t been conserved, issue that had origin different studies and opinions about its existence and authenticity.